Crystal structure of hexaaquazinc(II) 4-nitrobenzoate dihydrate, C14H24N2O16Zn - Shen Ye-Dan; Lin Jian-Li (Zeitschrift für Kristallographie - New Crystal Structures, 2013)
C14H24N2O16Zn, triclinic, P1̄ (no. 2), a = 5.980(1) Å, b = 7.363(2) Å, c = 12.360(3) Å, α = 97.90(3)°, β = 96.83(3)°, γ = 91.16(3)°, V = 534.9 Å3, Z = 1, Rgt(F) = 0.0439, wRref(F2) = 0.1315, T = 295 K.